2007
DOI: 10.2337/dc06-1501
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cord Insulin and Insulin-Related Peptides Suggests That Girls Are More Insulin Resistant Than Boys at Birth

Abstract: OBJECTIVE -We aimed to examine sex differences in insulin and insulin propeptide concentrations at birth using validated cord blood collection.RESEARCH DESIGN AND METHODS -We tested the impact on insulin and insulin propeptides of taking 13 cord blood samples in heparin and EDTA and then centrifuging and separating plasma after 1, 2, 24, or 48 h at room temperature (heparin) or 4°C (EDTA). Cord plasma insulin and insulin propeptides concentrations were measured in 440 babies and correlated with offspring anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 24 publications
(46 reference statements)
5
46
0
3
Order By: Relevance
“…These findings are in accordance with a previous study which found girls to be intrinsically more insulin resistance than boys at birth (Shields et al 2007). Despite weighing less at birth, the girls had significantly higher insulin and proinsulin concentrations in cord blood than boys, whereas there was no difference in cord glucose concentrations between girls and boys.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are in accordance with a previous study which found girls to be intrinsically more insulin resistance than boys at birth (Shields et al 2007). Despite weighing less at birth, the girls had significantly higher insulin and proinsulin concentrations in cord blood than boys, whereas there was no difference in cord glucose concentrations between girls and boys.…”
Section: Discussionsupporting
confidence: 82%
“…Despite weighing less at birth, the girls had significantly higher insulin and proinsulin concentrations in cord blood than boys, whereas there was no difference in cord glucose concentrations between girls and boys. the same study also found that girls had significantly more subcutaneous fat measured by triceps and subscapular skinfold thicknesses (Shields et al 2007). We preferred not to use relative birth weight in the present work.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In brief, mothers were seen by the research midwife at 28 weeks of gestation, and a fasting blood sample was taken for glucose and insulin measurement. Umbilical cord blood was obtained from the placental end of the cord after the placenta was delivered and centrifuged as soon as possible (18). Plasma aliquots were stored at Ϫ80°C.…”
Section: Normal Reference Populationmentioning
confidence: 99%
“…12 Beverly at al conducted a study on insulin, insulin resistance, insulin related peptides and found insulin concentrations to be significantly correlated with all measures like birth weight, length, head circumference and also found maternal glucose to be significantly associated with increased insulin concentration, reflecting that maternal glycemia was a major determinant of fetal insulin secretion. 13 Limitations of the study were the sample size was smaller and further studies with larger sample size and long term follow up is required to establish the effect of insulin levels at birth with metabolic effects occurring in later childhood and adolescents.…”
Section: Discussionmentioning
confidence: 99%